Contrast Enhancement of Medical Images: A Review - Singh, Shankar; Pal, Pravesh (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
This paper studies various research contributions in the field of contrast enhancement of medicalimages. Medical images such as X-rays, ultrasound and others are used in the analysis anddiagnosis process by physicians and radiologists. If the image quality is not good and contrast ispoor then the diagnosis result is badly affected. Therefore, this paper attempts to review theresearch papers on contrast enhancement and recommend some viable solution to the challengesin existing research works.